OPTIMIZATION OF TAXATION OF RESTAURANT BUSINESS ESTABLISHMENTS IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT - Stebliuk, N. F.; Horozhankina, N. A.; Nebaba, N. O.; Shapoval, K. O. (Systems and Technologies, 2026)
The article analyzes the taxation systems of restaurant businesses in Ukraine, considering their organizational and legal status. The purpose of the study is to substantiate the theoretical and methodological foundations for the use of mechanisms of tax optimization in restaurant business establishments in the context of sustainable development. The peculiarities of applying the simplified and general taxation systems are examined, along with the specifics of tax regulation in this sector. It is substantiated that the modern restaurant business requires effective tax mechanisms that ensure not only a reduction in the tax burden but also the financial stability of enterprises, promote the formation of social responsibility, and create conditions for investment in ecological practices. A scenario-based approach to determining the level of tax burden is proposed, demonstrating significant differences among enterprises operating under various organizational and legal forms and applying different tax regimes. The practical significance of the research lies in utilizing the proposed approach to select optimal taxation models for restaurant establishments in the context of sustainable development. This contributes to reducing the tax burden, enhancing financial stability, and adapting enterprises to modern challenges caused by the martial law. Prospects for further research involve the application of modeling optimization strategies as a vital tool for analyzing and forecasting the results of implementing tax measures.